2005
DOI: 10.1212/01.wnl.0000158284.41705.a5
|View full text |Cite
|
Sign up to set email alerts
|

Heads down

Abstract: Acute ischemic stroke patients may benefit from lower head-of-the-bed positions to promote residual blood flow to ischemic brain tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
139
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(148 citation statements)
references
References 21 publications
4
139
0
5
Order By: Relevance
“…4 Small, nonrandomized studies have indicated that the lying-flat position (i.e., fully supine with the back horizontal and the face upwards) increases blood flow in major arteries 5,6 and improves oxygenation of the brain, 7,8 whereas a sitting-up body position with the head elevated (hereafter referred to as the "sitting-up position") may reduce intracranial pressure in patients with large hemispheric ischemic stroke. 9 Uncertainty over the role of head positioning after acute stroke and the potential risks of cardiopulmonary dysfunction and aspiration pneumonia 10 have led to ambiguous guidelines 11 and variation in clinical practice.…”
mentioning
confidence: 99%
“…4 Small, nonrandomized studies have indicated that the lying-flat position (i.e., fully supine with the back horizontal and the face upwards) increases blood flow in major arteries 5,6 and improves oxygenation of the brain, 7,8 whereas a sitting-up body position with the head elevated (hereafter referred to as the "sitting-up position") may reduce intracranial pressure in patients with large hemispheric ischemic stroke. 9 Uncertainty over the role of head positioning after acute stroke and the potential risks of cardiopulmonary dysfunction and aspiration pneumonia 10 have led to ambiguous guidelines 11 and variation in clinical practice.…”
mentioning
confidence: 99%
“…Importantly, this treatment can be applied as soon as an ischemic stroke patient is diagnosed. When head position is reduced from 30° to 0° elevation during the first 24 hours after ischemic onset, the mean flow velocity of MCA (measured using Transcranial Doppler) is increased by 20%, resulting in functional improvement in 15% of patients (NIHSS) (Wojner-Alexander, 2005). Conversely, a decrease in cerebral blood flow was observed by increasing the head position from 0° to 30° or 45° Moraine et al, 2000), with cerebral blood flow determined according to the arteriovenous pressure gradient (Moraine et al, 2000).…”
Section: Augmenting Cerebral Blood Flow Using Head Positioningmentioning
confidence: 99%
“…Typically, a conservative approach is used to achieve "permissive hypertension," allowing the blood pressure to remain relatively high to maximize cerebral blood flow during a period of presumed impaired autoregulation. This approach includes the use of intravenous fluids for volume repletion, cessation of antihypertensive therapy, and keeping the head of the patient's bed flat for a period of time [23]. If a patient had fluctuating neurological symptoms (especially if correlated with relatively hypotensive episodes), then induced hypertension may be considered.…”
Section: Large Artery Atherothromboembolismmentioning
confidence: 99%